2022
DOI: 10.1101/2022.06.10.495618
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Salicaceae as potential host plants ofXylella fastidiosain European temperate regions

Abstract: The discovery of three subspecies of Xylella fastidiosa in Europe has triggered major attention on the potential spread up North of the bacteria. Assessing the susceptibility of a previously unexposed European flora is a key element that remains widely unknown. Under biosafety facility, we evaluated the susceptibility of Salicaceae such as Populus tremula, Populus canescens, Salix alba and Salix caprea by mechanically inoculating the KLN59.3 GFP-labelled X. fastidiosa at 22 C and at 28 C. Bacterial movement an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 60 publications
(72 reference statements)
0
0
0
Order By: Relevance
“…and A. grp. salicina were specialists, each thriving on almost only one plant family, confirming the biological informations available for these species (Casarin et al, 2021;Morente et al, 2018).…”
Section: Most Xylem Feeders Are Generalistssupporting
confidence: 63%
See 2 more Smart Citations
“…and A. grp. salicina were specialists, each thriving on almost only one plant family, confirming the biological informations available for these species (Casarin et al, 2021;Morente et al, 2018).…”
Section: Most Xylem Feeders Are Generalistssupporting
confidence: 63%
“…As a consequence, greater damage due to Pierce's disease was observed near rivers (Purcell, 2013). In Belgium, Casarin et al (2021) suggested that Salicaceae, abundant on river banks, hosted populations of vectors of Xf (especially Aphrophora grp. salicina).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation